Modernization and Standardization of Homoeopathic Education Globally: A LMHI Initiative (Homoeopathy for All, 2024)
Homoeopathy is  recognized globally, with the World  Health Organization (WHO) noting  its widespread use as a form of  Traditional Medicine (TM) in all  continents.  Despite its popularity,  homoeopathy faces challenges in  providing standardized education.  To modernize education, a unified,  evidence-based approach is needed,  incorporating scientific research,  interdisciplinary collaboration,  and continuous professional  development.  The LMHI (Liga Medicorum  Homoeopathica Internationalis), in  collaboration with European and  other global organizations, aims to  create an internationally acceptable  curriculum for homoeopathy. Standardizing education  globally can enhance the quality  of homoeopathic practice and  contribute to WHO's goals  for traditional medicine. The  homoeopathic community  is encouraged to join LMHI  to strengthen homoeopathy  globally. Qualified and registered  homoeopaths can now obtain  membership online at www.lmhi. org .
Keywords: presence; Complementary; popularity